The female handball player - Hansen, M.; Barner Dalgaard, L.; Zebis, M. K.; Gliemann, L.; Melin, A.; Klungland Torstveit, M. (Handball Sports Medicine, 2018)
Female hormones fluctuate in concentrations during the menstrual cycle. This has triggered speculations among athletes, coaches, as well as researchers about the hormonal changes that lead to variations in athletic performance and adaptation to training. Many athletes, as in the general population, use oral contraceptives. This has raised questions concerning the suppression of the endogenous circulating female hormones and if the administration of synthetic hormones may have negative impact on athletic performance and training adaptations - or the opposite.